2022
DOI: 10.3389/fnut.2022.923472
|View full text |Cite
|
Sign up to set email alerts
|

Beef intake and risk of rheumatoid arthritis: Insights from a cross-sectional study and two-sample Mendelian randomization

Abstract: BackgroundBeef is common in daily diet, but its association with the risk of rheumatoid arthritis (RA) remains uncertain. The objective of this study is to explore the relationship between beef intake and the risk of RA.Materials and methodsWe investigated the association between beef intake and risk of RA by multivariate logistic regression, based on the National Health and Nutrition Examination Survey (NHANES) 1999–2016 involving 9,618 participants. The dose–response relationship between beef intake and RA w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
1
2
0
Order By: Relevance
“…Meat intake, especially red meat, increases the risk of IA ( 17 ). The present study also found that beef intake increases the risk of RA, which has been confirmed in previous MR studies ( 50 ). It is puzzling that in a study of the causality of dietary factors in ReA, we found that intake of processed meat was a protective factor against the disease, which is generally considered to increase the risk of developing chronic disease, but previous studies have focused more on the association of processed meat with the risk of tumours, diabetes mellitus, and cardiovascular diseases ( 51 ).…”
Section: Discussionsupporting
confidence: 93%
“…Meat intake, especially red meat, increases the risk of IA ( 17 ). The present study also found that beef intake increases the risk of RA, which has been confirmed in previous MR studies ( 50 ). It is puzzling that in a study of the causality of dietary factors in ReA, we found that intake of processed meat was a protective factor against the disease, which is generally considered to increase the risk of developing chronic disease, but previous studies have focused more on the association of processed meat with the risk of tumours, diabetes mellitus, and cardiovascular diseases ( 51 ).…”
Section: Discussionsupporting
confidence: 93%
“…Carter et al [ 53 ] suggested that two repeated measurements are acceptable to give a better strength of diet–disease associations. However, only a few have used a minimum of two repeated datasets [ 10 , 18 , 23 , 32 , 33 , 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Several other non-communicable diseases have been studied, including gout [ 39 , 40 ], inflammatory bowel diseases [ 41 , 42 , 43 ], and rheumatoid arthritis [ 44 , 45 ]. In most of these studies, to find a correlation between different food groups and diseases, FFQ is used for dietary assessment.…”
Section: Resultsmentioning
confidence: 99%